Encouraging Optimal Aging through a Lifestyle Based on Islamic Psychospiritual Science - Che Zarrina Sa`ari; Hasimah Chik; Syed Mohammad Hilmi; Sharifah Basirah Syed Muhsin (International Journal of Nusantara Islam, 2023)
Ageing is an inevitable natural process that can give rise to concerns at both individual and societal levels if strategic planning is not in place to address the associated changes and ensure the well-being and satisfaction of this population. This article aims to explore the significance of healthcare for the elderly and the application of Islamic psychospiritual science in promoting healthy ageing by emphasizing lifestyle factors. The research employed a survey instrument administered to 307 randomly selected respondents, including elderly individuals and caregivers. The study was conducted across Malaysia from February 2022 to April 2022. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 22 software. The study findings indicate that all the elements encompassing an Islamic psychospiritual lifestyle, including the physical, psychological, spiritual, and social aspects, hold great significance. The Cronbach's alpha (α) score for this study was calculated at 0.934, indicating a high level of internal consistency. The results of this study offer valuable insights for family members, caregivers, welfare organizations, nursing homes, and other entities involved in elderly care. These findings can guide the optimization of care aspects, particularly in light of the challenges posed by the Covid-19 pandemic. Additionally, the study's outcomes can inform the development of modules or guidelines for elderly care, facilitating the caregiving process.